Application of potential phosphate-solubilizing bacteria and organic acids on phosphate solubilization from phosphate rock in aerobic rice - Panhwar, Qurban Ali; Jusop, Shamshuddin; Naher, Umme Aminun; Othman, Radziah; Ismail, Mohd Razi (Hindawi Publishing Corporation, 2013)
A study was conducted at Universiti Putra Malaysia to determine the effect of phosphate-solubilizing bacteria (PSB) and organic acids (oxalic & malic) on phosphate (P) solubilization from phosphate rock (PR) and growth of aerobic rice. Four rates of each organic acid (0, 10, 20, and 30 mM), and PSB strain (Bacillus sp.) were applied to aerobic rice. Total bacterial populations, amount of P solubilization, P uptake, soil pH, and root morphology were determined. The results of the study showed significantly high P solubilization in PSB with organic acid treatments. Among the two organic acids, oxalic acid was found more effective compared to malic acid. Application of oxalic acid at 20 mM along with PSB16 significantly increased soluble soil P (28.39 mg kg−1), plant P uptake (0.78 P pot−1), and plant biomass (33.26 mg). Addition of organic acids with PSB and PR had no influence on soil pH during the planting period. A higher bacterial population was found in rhizosphere (8.78 log10 cfu g−1) compared to the nonrhizosphere and endosphere regions. The application of organic acids along with PSB enhanced soluble P in the soil solution, improved root growth, and increased plant biomass of aerobic rice seedlings without affecting soil pH.